Resin molded article and resin molding material

The resin molded body with a thermosetting resin, graphite powder, and glass fibers addresses the challenges of electromagnetic wave attenuation and heat resistance, while suppressing polymerization and shrinkage, resulting in uniform and effective electromagnetic wave attenuation.

JP2025040598APending Publication Date: 2025-03-25DIC CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023147501
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-12
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

Existing resin molded bodies with electromagnetic wave damping layers face challenges in achieving excellent electromagnetic wave attenuation and heat resistance while minimizing polymerization and shrinkage issues, which can lead to irregularities in electromagnetic wave attenuation performance.

Method used

A resin molded body with an electromagnetic wave attenuation layer composed of a thermosetting resin, graphite powder with an average volume diameter of 200 μm or less, and glass fibers, where the graphite powder content is between 2% to 20% and the glass fiber content is between 25% to 55% by mass, effectively suppressing polymerization and shrinkage.

Benefits of technology

The proposed solution achieves excellent electromagnetic wave attenuation and heat resistance, ensuring uniform performance across the resin molded body while preventing polymerization and shrinkage issues.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025040598000001_ABST
    Figure 2025040598000001_ABST
Patent Text Reader

Abstract

To provide a resin molded article that exhibits both excellent attenuation of electromagnetic waves and superior heat resistance, and to further provide a resin molding material that exhibits both excellent attenuation of electromagnetic waves and superior heat resistance and also demonstrates excellent suppression of polymerization shrinkage.SOLUTION: A resin molded article comprises an electromagnetic wave attenuation layer including a thermosetting resin, graphite powder, and glass fiber, wherein the volume-average particle diameter of the graphite powder is 20 nm or more and 200 μm or less, the content of the graphite powder is 2 mass% or more and 20 mass% or less based on the total mass of the electromagnetic wave attenuation layer, and the content of the glass fiber is 25 mass% or more and 55 mass% or less based on the total mass of the electromagnetic wave attenuation layer.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin molding and a resin molding material. [Background technology]

[0002] Conventionally, electromagnetic shielding has been used to prevent electromagnetic noise leaking from electronic devices such as personal computers by using electronic devices with metal cases or metal-plated plastics. In particular, nowadays, it is becoming increasingly important to take measures against electromagnetic waves emitted by electronic components and high-frequency circuits that cause the devices to malfunction (so-called auto-poisoning). In the field of automobiles, where electronic control is highly advanced, millimeter-wave radars are used for the purpose of autonomous driving and collision damage reduction, and it is necessary to prevent auto-poisoning of high-frequency circuits inside the radar device housing.

[0003] For example, Patent Document 1 discloses an electromagnetic shielding material produced by pressing a resin molding material obtained by mixing a thermoplastic resin with carbon nanotubes and carbon black as electromagnetic shielding materials. According to Patent Document 1, the electromagnetic shielding material is capable of attenuating electromagnetic waves in the frequency band of 60 to 110 GHz.

[0004] On the other hand, Non-Patent Document 1 states that when handling high-frequency and high-power radio waves, there is a concern that the heat generated by the conversion of radio wave energy inside the absorber as a result of radio wave absorption may cause deformation of the carrier, such as resin or rubber, or cause smoke or fire.

[0005] Therefore, in order to improve the heat resistance of a resin molded article having an electromagnetic wave attenuation layer, it is conceivable to use a thermosetting resin instead of a thermoplastic resin.

[0006] However, when a resin molding material containing a mixture of a thermosetting resin, carbon nanotubes, and carbon black is pressed, it is difficult to obtain a resin molding of a desired thickness due to polymerization shrinkage. Furthermore, during press processing, the resin molding material flows out of the mold, making it impossible to apply a predetermined pressure to the resin molding material in the mold, and air bubbles are generated in the resin molding. When air bubbles are present in the resin molding, the electromagnetic wave attenuation property is reduced in the area where the air bubbles are present, and the electromagnetic wave attenuation performance of the resin molding may become uneven. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] International Publication No. 2019 / 235561 [Non-patent literature]

[0008] [Non-Patent Document 1] Yoshihiko Okada, "Alumina-carbon millimeter wave absorbing material", Journal of the Society of Inorganic Materials, Japan, Vol. 13, pp. 533-537, 2006. Summary of the Invention [Problem to be solved by the invention]

[0009] An object of the present invention is to provide a resin molding having excellent electromagnetic wave attenuation and heat resistance, and further to provide a resin molding material having excellent electromagnetic wave attenuation and heat resistance as well as excellent suppression of polymerization shrinkage. [Means for solving the problem]

[0010] The resin molded body according to the present invention comprises an electromagnetic wave attenuation layer containing a thermosetting resin, graphite powder, and glass fibers, the graphite powder having a volume average particle size of 200 μm or less, the graphite powder content being 2 mass% or more and 20 mass% or less based on the total mass of the electromagnetic wave attenuation layer, and the glass fiber content being 25 mass% or more and 55 mass% or less based on the total mass of the electromagnetic wave attenuation layer.

[0011] Moreover, the resin molding material according to the present invention is a resin molding material containing a thermosetting resin, graphite powder, and glass fibers, characterized in that the graphite powder has a volume average particle size of 200 μm or less, the graphite powder content is 2 mass% or more and 20 mass% or less based on the total mass of the resin molding material, and the glass fiber content is 25 mass% or more and 55 mass% or less based on the total mass of the resin molding material. Effect of the Invention

[0012] According to the present invention, it is possible to provide a resin molding having excellent electromagnetic wave attenuation and heat resistance, and further to provide a resin molding material having excellent electromagnetic wave attenuation and heat resistance as well as excellent suppression of polymerization shrinkage. [Brief description of the drawings]

[0013] [Figure 1] FIG. 2 is a schematic cross-sectional view showing one embodiment of a resin molded body. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] Hereinafter, an embodiment of the present invention will be described. One embodiment of the present invention is a resin molded body having an electromagnetic wave attenuation layer containing a thermosetting resin, graphite powder, and glass fiber, the volume average particle size of the graphite powder being 200 μm or less, the content of the graphite powder being 2% by mass or more and 20% by mass or less based on the total mass of the electromagnetic wave attenuation layer, and the content of the glass fiber being 25% by mass or more and 55% by mass or less based on the total mass of the electromagnetic wave attenuation layer. The electromagnetic wave attenuation layer of the resin molded body is obtained by molding a resin molding material (hereinafter also referred to as "resin molding material (1)") described below that contains a thermosetting resin, graphite powder, and glass fiber. That is, another embodiment of the present invention is a resin molding material used for the resin molded body (more specifically, the electromagnetic wave attenuation layer), which contains a thermosetting resin, graphite powder, and glass fiber.

[0015] The electromagnetic wave attenuation layer (hereinafter, simply referred to as "attenuation layer") is a layer capable of attenuating incident electromagnetic energy. More specifically, a resin molded product having an electromagnetic wave attenuation layer can attenuate electromagnetic waves of 30 GHz or more, preferably 40 GHz or more, 50 GHz or more, or 60 GHz or more, and can attenuate electromagnetic waves of 300 GHz or less, preferably 200 GHz or less, 100 GHz or less, or 90 GHz or less.

[0016] When the electromagnetic wave return loss of the resin molding is measured according to the description in the "Measurement of Electromagnetic Wave Attenuation" in the Examples below, the peak of the electromagnetic wave return loss in the frequency range of 60 to 90 GHz is preferably -5 dB or more, more preferably -10 dB or more, -15 dB or more, or -20 dB or more.

[0017] Furthermore, when the electromagnetic wave transmission attenuation of the resin molding is measured according to "Measurement of Electromagnetic Wave Attenuation" in the Examples below, it is preferable that the electromagnetic wave transmission attenuation is -40 dB or more, -50 dB or more, -60 dB or more, or -85 dB or more over the entire frequency range of 60 to 90 GHz.

[0018] In one embodiment of the present invention, the thermosetting resin contained in the damping layer and the resin molding material (1) may be any commonly used one and is not particularly limited, but is preferably an epoxy resin or a vinyl ester resin, since a molded body with higher strength can be obtained. In this case, the damping layer provided on the resin molding and the resin molding material (1) may be a cured product of a resin composition (details will be described later) containing the thermosetting resin. From the viewpoints of ease of work and ease of handling, the resin molding material (1) is preferably a sheet molding compound (hereinafter sometimes referred to as "SMC") or a prepreg.

[0019] The resin composition is not particularly limited and can be arbitrarily selected depending on the desired physical properties of the molded product, the application, etc. Hereinafter, the epoxy resin composition and the vinyl ester resin composition will be described in detail.

[0020] The epoxy resin composition is a thermosetting resin composition containing an epoxy group-containing compound and a curing agent or a curing accelerator. The epoxy group-containing compound is not particularly limited in its specific structure as long as it has an epoxy group in its molecular structure, and a wide variety of compounds can be used, and one type may be used alone, or two or more types may be used in combination. Among them, the epoxy group-containing compound is preferably a compound having two or more epoxy groups in its molecular structure, since it becomes an epoxy resin composition having excellent curing reaction. The ratio of the compound having two or more epoxy groups in the molecular structure to the entire epoxy group-containing compound is preferably 80% by mass or more, and particularly preferably 90% by mass or more.

[0021] Examples of the epoxy group-containing compound include diglycidyloxybenzene, diglycidyloxynaphthalene, biphenol-type epoxy resins, bisphenol-type epoxy resins, polyglycidyl ethers of aliphatic polyols, novolac-type epoxy resins, alicyclic epoxy resins, glycidylamine-type epoxy resins, heterocyclic epoxy resins, glycidyl ester-type epoxy resins, triphenolmethane-type epoxy resins, phenol or naphthol aralkyl-type epoxy resins, phenylene or naphthylene ether-type epoxy resins, oxolidone-modified epoxy resins, brominated epoxy resins thereof, and epoxy resins obtained by extending these epoxy group-containing compounds with an extender.

[0022] Examples of the biphenol type epoxy resin include biphenol compounds such as biphenol and tetramethylbiphenol, and polyglycidyl ethers of one or more alkylene oxide adducts of these biphenol compounds with epihalohydrin.

[0023] Examples of the bisphenol type epoxy resin include bisphenol compounds such as bisphenol A, bisphenol F, bisphenol S, bisphenol fluorene, and biscresol fluorene, and polyglycidyl ethers of one or more alkylene oxide adducts of these bisphenol compounds with epihalohydrin.

[0024] Examples of the polyglycidyl ether of the aliphatic polyol include polyglycidyl ethers of various aliphatic polyol compounds and one or more of these alkylene oxide adducts with epihalohydrin. Examples of the aliphatic polyol compound include ethylene glycol, propylene glycol, 1,3-propanediol, 2-methylpropanediol, 1,2,2-trimethyl-1,3-propanediol, 2,2-dimethyl-3-isopropyl-1,3-propanediol, 1,4-butanediol, 1,3-butanediol, 3-methyl-1,3-butanediol, 1,5-pentanediol, 3-methyl-1,5-pentanediol, neopentyl glycol, Examples of the diol compounds include aliphatic diol compounds such as 1,6-hexanediol, 1,4-bis(hydroxymethyl)cyclohexane, and 2,2,4-trimethyl-1,3-pentanediol; alicyclic diol compounds such as 2,2-bis(4-hydroxyphenyl)propane; and aliphatic polyol compounds with three or more functional groups such as trimethylolethane, trimethylolpropane, glycerin, hexanetriol, pentaerythritol, ditrimethylolpropane, and dipentaerythritol.

[0025] Examples of the novolac type epoxy resin include novolac resins formed by polyglycidyl etherifying one or more of various phenolic compounds such as phenol, dihydroxybenzene, cresol, xylenol, naphthol, dihydroxynaphthalene, bisphenol, and biphenol with epihalohydrin.

[0026] Examples of the alicyclic epoxy resin include those obtained by hydrogenating the biphenol compounds or bisphenol compounds, and those obtained by polyglycidyl etherifying one or more of the alkylene oxide adducts thereof with epihalohydrin, as well as 3,4-epoxy-6-methylcyclohexylmethyl-3,4-epoxy-6-methylcyclohexanecarboxylate, 1-epoxyethyl-3,4-epoxycyclohexane, and the like.

[0027] Examples of the glycidylamine type epoxy resin include N,N-diglycidylaniline, triglycidylaminophenol, tetraglycidylxylenediamine, and 4,4'-methylenebis[N,N-diglycidylaniline].

[0028] Examples of the heterocyclic epoxy resin include 1,3-diglycidyl-5,5-dimethylhydantoin and triglycidyl isocyanurate.

[0029] Examples of the glycidyl ester type epoxy resin include diglycidyl phthalate, diglycidyl tetrahydrophthalate, diglycidyl-p-oxybenzoate, and glycidyl dimerate.

[0030] Examples of the extender for the epoxy resin include the above-mentioned various biphenol compounds and hydrogenated products thereof, the above-mentioned various bisphenol compounds and hydrogenated products thereof, dibasic acid compounds, and acid group-containing polyester resins.

[0031] Among these, the epoxy resin is preferably the bisphenol type epoxy resin, and more preferably a bisphenol type epoxy resin having an epoxy equivalent in the range of 160 to 260 g / equivalent, because it is excellent in strength of the molded product and impregnation into glass fiber. The ratio of the bisphenol type epoxy resin to the entire epoxy group-containing compound is preferably 40 mass% or more, more preferably 60 mass% or more, and particularly preferably 70 mass% or more. The ratio is preferably 95 mass% or less, and more preferably 90 mass% or less.

[0032] From the viewpoint of decreasing the viscosity of the epoxy resin, the epoxy resin composition preferably contains the polyglycidyl ether of the aliphatic polyol, more preferably the polyglycidyl ether of an aliphatic polyol having 2 to 6 carbon atoms. The proportion of the polyglycidyl ether of the aliphatic polyol in the entire epoxy group-containing compound is preferably 5% by mass or more, more preferably 10% by mass or more. The proportion is preferably 50% by mass or less, more preferably 35% by mass or less.

[0033] When the bisphenol type epoxy resin and the polyglycidyl ether of the aliphatic polyol are used in combination, the mass ratio of the two (bisphenol type epoxy resin) / (polyglycidyl ether of the aliphatic polyol) is preferably in the range of 60 / 40 to 95 / 5, and more preferably in the range of 70 / 30 to 85 / 15.

[0034] As the curing agent or curing accelerator, various compounds generally used as curing agents or curing accelerators for epoxy group-containing compounds can be used without any particular limitation. The curing agent or curing accelerator may be used alone or in combination of two or more kinds.

[0035] Examples of the curing agent or curing accelerator include amine compounds, amide compounds, acid anhydrides, phenolic hydroxyl group-containing compounds, phosphorus compounds, imidazole compounds, imidazoline compounds, urea compounds, organic acid metal salts, Lewis acids, and amine complex salts.

[0036] Examples of the amine compound include aliphatic amine compounds such as ethylenediamine, tetramethylethylenediamine, diethylenetriamine, hexamethylenediamine, triethylenetetramine, and guanidine derivatives; alicyclic and heterocyclic amine compounds such as piperidine, piperazine, isophoronediamine, and 1,8-diazabicyclo-[5.4.0]-undecene (DBU); aromatic amine compounds such as phenylenediamine, diaminodiphenylmethane, diaminodiphenylsulfone, benzylmethylamine, dimethylbenzylamine, xylylenediamine, and pyridine; and boron trifluoride amine complexes.

[0037] Examples of the amide compound include dicyandiamide and polyamidoamine. Examples of the polyamidoamine include those obtained by reacting an aliphatic dicarboxylic acid such as succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, or azelaic acid, or a carboxylic acid compound such as a fatty acid or a dimer acid, with an aliphatic polyamine or a polyamine having a polyoxyalkylene chain.

[0038] Examples of the acid anhydride include phthalic anhydride, trimellitic anhydride, pyromellitic anhydride, maleic anhydride, tetrahydrophthalic anhydride, methyltetrahydrophthalic anhydride, methylnadic anhydride, hexahydrophthalic anhydride, and methylhexahydrophthalic anhydride.

[0039] Examples of the phenolic hydroxyl group-containing resin include various novolak resins, dicyclopentadiene-phenol addition type resins, phenol or naphthol aralkyl resins, triphenolmethane resins, phenol or naphthol aralkyl resins, phenylene or naphthylene ether resins, and aminotriazine-modified phenol resins.

[0040] Examples of the phosphorus compound include alkyl phosphines such as ethylphosphine and butylphosphine, primary phosphines such as phenylphosphine, dialkyl phosphines such as dimethylphosphine and dipropylphosphine, secondary phosphines such as diphenylphosphine and methylethylphosphine, and tertiary phosphines such as trimethylphosphine, triethylphosphine and triphenylphosphine.

[0041] Examples of the imidazole compound include imidazole, 1-methylimidazole, 2-methylimidazole, 3-methylimidazole, 4-methylimidazole, 5-methylimidazole, 1-ethylimidazole, 2-ethylimidazole, 3-ethylimidazole, 4-ethylimidazole, 5-ethylimidazole, 1-n-propylimidazole, 2-n-propylimidazole, 1-isopropylimidazole, 2 -Isopropylimidazole, 1-n-butylimidazole, 2-n-butylimidazole, 1-isobutylimidazole, 2-isobutylimidazole, 2-undecyl-1H-imidazole, 2-heptadecyl-1H-imidazole, 1,2-dimethylimidazole, 1,3-dimethylimidazole, 2,4-dimethylimidazole, 2-ethyl-4-methylimidazole, 1-phenylimidazole, 2-phenyl-1H- Imidazole, 4-methyl-2-phenyl-1H-imidazole, 2-phenyl-4-methylimidazole, 1-benzyl-2-methylimidazole, 1-benzyl-2-phenylimidazole, 1-cyanoethyl-2-methylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-phenylimidazole, 2-phenylimidazole Examples of the isocyanuric acid adduct include isocyanuric acid adduct, 2-methylimidazole isocyanuric acid adduct, 2-phenyl-4,5-dihydroxymethylimidazole, 2-phenyl-4-methyl-5-hydroxymethylimidazole, 1-cyanoethyl-2-phenyl-4,5-di(2-cyanoethoxy)methylimidazole, 1-dodecyl-2-methyl-3-benzylimidazolium chloride, and 1-benzyl-2-phenylimidazole hydrochloride.

[0042] Examples of the imidazoline compound include 2-methylimidazoline and 2-phenylimidazoline.

[0043] Examples of the urea compound include p-chlorophenyl-N,N-dimethylurea, 3-phenyl-1,1-dimethylurea, 3-(3,4-dichlorophenyl)-N,N-dimethylurea, N-(3-chloro-4-methylphenyl)-N',N'-dimethylurea, and 4,4'-methylenebisphenyldimethylurea.

[0044] Among these, the curing agent or curing accelerator is preferably an amine compound, an amide compound, an imidazole compound, or a urea compound, since it cures quickly and gives a cured product with excellent strength.

[0045] The amount of the curing agent or curing accelerator in the epoxy resin composition is preferably in the range of 0.5 to 1.2 moles of functional group or active hydrogen in the curing agent per mole of epoxy group in the epoxy group-containing compound when using a compound having a functional group that can react with an epoxy group, such as an amine compound, an amide compound, an acid anhydride, or a phenolic hydroxyl group-containing compound. Also, when using a phosphorus compound, an imidazole compound, an imidazoline compound, a urea-based compound, or the like, it is preferable to mix the curing agent or curing accelerator in a ratio of 0.5 to 20 parts by mass per 100 parts by mass of the epoxy group-containing compound.

[0046] The epoxy resin composition may contain other components other than the epoxy group-containing compound and the curing agent or curing accelerator. Examples of other components include curable compounds other than the epoxy group-containing compound, curing agent, or curing accelerator, curing catalysts, water absorbents, thermoplastic resins, inorganic fillers, low shrinkage agents, mold release agents, thickeners, viscosity reducers, pigments, antioxidants, plasticizers, flame retardants, antibacterial agents, ultraviolet stabilizers, reinforcing materials, etc. These other components are added appropriately depending on the desired performance and applications of the sheet molding compound, and the amount of addition is also arbitrary.

[0047] In particular, the epoxy resin composition preferably further contains a polyhydroxy compound and a polyisocyanate compound, since a sheet molding compound having excellent handling properties such as peelability from the carrier film can be obtained. In this case, the total mass of the epoxy group-containing compound, the curing agent or curing accelerator, the polyhydroxy compound, and the polyisocyanate compound in the epoxy resin composition is preferably 80 mass% or more, and particularly preferably 90 mass% or more.

[0048] The polyhydroxy compound is not particularly limited in its specific structure, and a wide variety of compounds can be used as long as it has a plurality of hydroxyl groups in its molecular structure. The polyhydroxy compound may be used alone or in combination of two or more kinds. In this specification, the polyhydroxy compound having an epoxy group is treated as the epoxy group-containing compound.

[0049] Examples of the polyhydroxy compound include aliphatic polyol compounds, dihydroxybenzenes, dihydroxynaphthalenes, trihydroxybenzenes, trihydroxynaphthalenes, triphenol alkanes, biphenol compounds, bisphenol compounds, alicyclic polyol compounds, novolak resins, phenol or naphthol aralkyl resins, phenylene or naphthylene ether resins, and alkylene oxide adducts thereof.

[0050] Examples of the aliphatic polyol compound include ethylene glycol, propylene glycol, 1,3-propanediol, 2-methylpropanediol, 1,2,2-trimethyl-1,3-propanediol, 2,2-dimethyl-3-isopropyl-1,3-propanediol, 1,4-butanediol, 1,3-butanediol, 3-methyl-1,3-butanediol, 1,5-pentanediol, 3-methyl-1,5-pentanediol, and neopentyl glycol. aliphatic diol compounds such as 1,6-hexanediol, 1,4-bis(hydroxymethyl)cyclohexane, and 2,2,4-trimethyl-1,3-pentanediol; alicyclic diol compounds such as 2,2-bis(4-hydroxyphenyl)propane; and aliphatic polyol compounds with three or more functional groups such as trimethylolethane, trimethylolpropane, glycerin, hexanetriol, pentaerythritol, ditrimethylolpropane, and dipentaerythritol.

[0051] Examples of the biphenol compound include biphenol and tetramethylbiphenol.

[0052] Examples of the bisphenol compound include bisphenol A, bisphenol F, bisphenol S, bisphenol fluorene, and biscresol fluorene.

[0053] Examples of the alicyclic polyol compound include cyclohexanediol and hydrogenated biphenol compounds and bisphenol compounds.

[0054] Examples of the novolak type resin include novolak resins made of one or more of various phenolic compounds such as phenol, dihydroxybenzene, cresol, xylenol, naphthol, dihydroxynaphthalene, bisphenol, and biphenol.

[0055] Among them, it is preferable to use a polyhydroxy compound having a hydroxyl equivalent in the range of 125 to 600 g / equivalent, since it is possible to obtain a sheet molding compound having excellent handling properties such as peelability from a carrier film, and it is more preferable that the ratio of polyhydroxy compounds having a hydroxyl equivalent in the range of 125 to 600 g / equivalent to the total polyhydroxy compounds is 70% by mass or more, and it is particularly preferable that the ratio is 80% by mass or more. In addition, the polyhydroxy compound is preferably one having a (poly)alkylene oxide structure in its molecular structure, more preferably an alkylene oxide adduct of the aliphatic polyol compound or the bisphenol compound, and more preferably an aliphatic polyol compound having 2 to 6 carbon atoms. In addition, it is more preferable that the hydroxyl equivalent is in the range of 150 to 400 g / equivalent.

[0056] In addition, the amount of the polyhydroxy compound is preferably 5 parts by mass or more, and more preferably 10 parts by mass or more, and is preferably 50 parts by mass or less, and more preferably 30 parts by mass or less, relative to 100 parts by mass of the epoxy group-containing compound, in order to obtain a sheet molding compound having excellent handleability, such as strength of the molded product and peelability from the carrier film.

[0057] The polyisocyanate compound may have any of a wide variety of structures without any particular limitations, so long as it has a plurality of isocyanate groups in its molecular structure. The polyisocyanate compound may be used alone or in combination of two or more. Specific examples include aliphatic diisocyanate compounds such as butane diisocyanate, pentamethylene diisocyanate, hexamethylene diisocyanate, 2,2,4-trimethylhexamethylene diisocyanate, 2,4,4-trimethylhexamethylene diisocyanate, and dimer acid diisocyanate; alicyclic diisocyanate compounds such as norbornane diisocyanate, isophorone diisocyanate, hydrogenated xylylene diisocyanate, and hydrogenated diphenylmethane diisocyanate; toluene diisocyanate, and xylylene diisocyanate. aromatic diisocyanate compounds such as tetramethylxylylene diisocyanate, tolidine diisocyanate, diphenylmethane diisocyanate, 1,5-naphthalene diisocyanate, and polymethylene polyphenyl polyisocyanate; modified products of these isocyanate compounds, such as isocyanurate modified products, biuret modified products, allophanate modified products, carbodiimide modified products, and urethane imine modified products, as well as polyol modified products modified with a polyol having a number average molecular weight of 1,000 or less, such as diethylene glycol or dipropylene glycol.

[0058] Among these, aromatic polyisocyanate compounds or various modified products thereof are preferred because they can provide a sheet molding compound that is excellent in handling properties such as peelability from the carrier film, etc. The isocyanate group content is preferably 15% by mass or more, more preferably 20% by mass or more, and is preferably 40% by mass or less.

[0059] The amount of the polyisocyanate compound added is preferably 0.5 or more, more preferably 0.8 or more, in terms of the mole number of isocyanate groups in the polyisocyanate compound per mole of hydroxyl groups in the polyhydroxy compound, since a sheet molding compound having excellent handling properties such as peelability from a carrier film can be obtained, and is preferably 3.0 or less, more preferably 1.5 or less, and particularly preferably 1.2 or less.

[0060] When the epoxy resin composition contains the polyisocyanate compound or the polyol compound, a urethanization catalyst or a water absorbing agent may be added as necessary. The urethanization catalyst may be used alone or in combination of two or more. Examples of the urethanization catalyst include amine compounds such as triethylamine, dibutylamine, triethylenediamine, and pyridine; phosphorus compounds such as triphenylphosphine and triethylphosphine; organic tin compounds such as dibutyltin dilaurate, octyltin trilaurate, octyltin diacetate, dibutyltin diacetate, and tin octylate; organic zinc compounds such as zinc amine, zinc carboxylate, zinc stearate, and zinc octylate; organic bismuth compounds such as bismuth carboxylate; organic zirconium compounds such as zirconium acetylacetonate and zirconium tetraethanolate; organic aluminum compounds such as aluminum triethoxide; and organic titanium compounds such as titanium tetrabutylate and titanium ethylacetoacetate. Among them, organic zinc compounds and organic bismuth compounds are preferred because they are safer to living organisms and have better storage stability.

[0061] When the urethanization catalyst is used, the amount added is preferably in the range of 0.002 to 1 mass %, more preferably in the range of 0.01 to 0.8 mass %, based on the total mass of the epoxy group-containing compound, the curing agent or curing accelerator, the polyhydroxy compound, and the polyisocyanate compound.

[0062] The water absorbing agent may be used alone or in combination of two or more kinds. Examples of the water absorbing agent include silica gel, activated alumina, and molecular sieves. Among these, molecular sieves are preferred because of their excellent water absorption efficiency. The pore size is preferably in the range of 0.1 to 0.5 nm, and more preferably in the range of 0.2 to 0.4 nm. The particle size is preferably 50 um or less, and more preferably 10 um or less. When the water absorbing agent is used, the amount of the water absorbing agent added is preferably in the range of 0.1 to 5 mass% based on the total mass of the epoxy group-containing compound, the curing agent or curing accelerator, the polyhydroxy compound, and the polyisocyanate compound.

[0063] In order to obtain excellent impregnation ability into glass fibers, the viscosity of the epoxy resin composition at 25°C is preferably 100 mPa·s or more, more preferably 300 mPa·s or more, and is preferably 10,000 mPa·s or less, more preferably 6,000 mPa·s or less. In this specification, the viscosity of the epoxy resin composition is measured within 10 minutes after all the ingredients of the epoxy resin composition are mixed.

[0064] The vinyl ester resin composition is a thermosetting resin composition containing a vinyl ester resin. Examples of vinyl ester resins include those using an epoxy group-containing compound and (meth)acrylic acid as reaction raw materials. One type of vinyl ester resin may be used alone, or two or more types may be used in combination. In this specification, "(meth)acrylic acid" refers to either or both of acrylic acid and methacrylic acid, and "(meth)acrylate" refers to either or both of acrylate and methacrylate.

[0065] The epoxy group-containing compound that is the reaction raw material of the vinyl ester resin may be any of the various compounds exemplified above as those contained in the epoxy resin composition. Among them, the bisphenol type epoxy resin or the epoxy resin obtained by elongating the bisphenol type epoxy resin with an elongating agent is preferred because of its excellent strength of the molded product and its impregnation into glass fiber. The epoxy equivalent of the bisphenol type epoxy resin or the epoxy resin obtained by elongating the bisphenol type epoxy resin with an elongating agent is preferably 160 g / equivalent or more, more preferably 170 g / equivalent or more, and is preferably 400 g / equivalent or less, more preferably 380 g / equivalent or less.

[0066] The reaction between the epoxy group-containing compound and (meth)acrylic acid can be carried out by heating at a temperature of about 60 to 140°C in the presence of any esterification catalyst. If necessary, a reaction solvent or a polymerization inhibitor may be added. In addition, the reaction ratio of the epoxy group-containing compound and (meth)acrylic acid is preferably such that the molar ratio of the functional groups of both [carboxy group / epoxy group] is in the range of 0.6 to 1.1 in order to obtain a vinyl ester resin with an excellent balance of performance such as impregnation ability into glass fiber and curing ability. When multiple types of the vinyl ester resin are used in combination, multiple epoxy group-containing compounds may be (meth)acrylated together, or each may be (meth)acrylated separately and mixed.

[0067] The proportion of the vinyl ester resin using the bisphenol-type epoxy resin or the epoxy resin obtained by elongating the bisphenol-type epoxy resin with an elongator as a reaction raw material in the entire vinyl ester resin is preferably 70 mass % or more, more preferably 80 mass % or more, and particularly preferably 90 mass % or more.

[0068] The vinyl ester resin composition may contain other components other than the vinyl ester resin composition. Examples of other components include polymerizable unsaturated group-containing compounds other than the vinyl ester resin, polyisocyanate compounds, curing catalysts, water absorbents, thermoplastic resins, inorganic fillers, shrinkage reducing agents, release agents, thickeners, viscosity reducers, pigments, antioxidants, plasticizers, flame retardants, antibacterial agents, ultraviolet stabilizers, reinforcing materials, etc. These other components are added appropriately according to the desired performance and applications of the sheet molding compound, and the amount of addition is also arbitrary.

[0069] Among them, it is preferable to use a polymerizable unsaturated group-containing compound other than the vinyl ester resin, because it is excellent in strength of the molded product and impregnation into glass fiber. The polymerizable unsaturated group-containing compound may be used alone or in combination of two or more. When using a polymerizable unsaturated group-containing compound, the ratio of the polymerizable unsaturated group-containing compound to the total of 100 parts by mass of the thermosetting resin and the polymerizable unsaturated group-containing compound is preferably 15% by mass or more, more preferably 30% by mass or more, and preferably 70% by mass or less, more preferably 60% by mass or less, and particularly preferably 50% by mass or less.

[0070] Examples of the polymerizable unsaturated group-containing compound include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, octyl (meth)acrylate, isodecyl (meth)acrylate, lauryl (meth)acrylate, isotridecyl (meth)acrylate, n-stearyl (meth)acrylate, ethylene glycol (meth)acrylate alkyl ether, propylene glycol Aliphatic mono(meth)acrylate compounds such as chol(meth)acrylate alkyl ether; alicyclic mono(meth)acrylate compounds such as cyclohexyl(meth)acrylate, isobornyl(meth)acrylate, adamantyl mono(meth)acrylate, dicyclopentenyloxyethyl(meth)acrylate, dicyclopentanyl methacrylate; heterocyclic mono(meth)acrylate compounds such as glycidyl(meth)acrylate, tetrahydrofurfuryl acrylate; benzyl(meth)acrylate, phenyl(meth)acrylate, phenyl(meth)acrylate, aromatic ring-containing mono(meth)acrylate compounds such as phenylbenzyl (meth)acrylate, phenoxy (meth)acrylate, phenoxyethyl (meth)acrylate, phenoxyethoxyethyl (meth)acrylate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, phenoxybenzyl (meth)acrylate, benzyl benzyl (meth)acrylate, and phenylphenoxyethyl (meth)acrylate; ) (poly)oxyalkylene-modified mono(meth)acrylate compounds having a polyoxyalkylene chain such as an oxytetramethylene chain introduced therein; lactone-modified mono(meth)acrylate compounds having a (poly)lactone structure introduced into the molecular structure of the various mono(meth)acrylate compounds mentioned above; aliphatic di(meth)acrylate compounds such as ethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, butanediol di(meth)acrylate, hexanediol di(meth)acrylate, and neopentyl glycol di(meth)acrylate;Alicyclic di(meth)acrylate compounds such as 1,4-cyclohexanedimethanol di(meth)acrylate, norbornane di(meth)acrylate, norbornane dimethanol di(meth)acrylate, dicyclopentanyl di(meth)acrylate, and tricyclodecane dimethanol di(meth)acrylate; aromatic ring-containing di(meth)acrylate compounds such as biphenol di(meth)acrylate and bisphenol di(meth)acrylate; and compounds having (poly)oxyethylene in the molecular structure of the above di(meth)acrylate compounds. polyoxyalkylene-modified di(meth)acrylate compounds having a (poly)oxyalkylene chain such as a propylene chain, a (poly)oxypropylene chain, or a (poly)oxytetramethylene chain introduced therein; lactone-modified di(meth)acrylate compounds having a (poly)lactone structure introduced into the molecular structure of the above-mentioned various di(meth)acrylate compounds; aliphatic tri(meth)acrylate compounds such as trimethylolpropane tri(meth)acrylate and glycerin tri(meth)acrylate; (Poly)oxyalkylene-modified tri(meth)acrylate compounds in which a (poly)oxyalkylene chain such as a (poly)oxyethylene chain, a (poly)oxypropylene chain, or a (poly)oxytetramethylene chain has been introduced into the aliphatic tri(meth)acrylate compound; lactone-modified tri(meth)acrylate compounds in which a (poly)lactone structure has been introduced into the molecular structure of the aliphatic tri(meth)acrylate compound; pentaerythritol tetra(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate aliphatic poly(meth)acrylate compounds having 4 or more functional groups, such as tetrafunctional or higher functional poly(meth)acrylates; (poly)oxyalkylene-modified poly(meth)acrylate compounds having 4 or more functional groups in which a (poly)oxyalkylene chain, such as a (poly)oxyethylene chain, a (poly)oxypropylene chain, or a (poly)oxytetramethylene chain, has been introduced into the molecular structure of the aliphatic poly(meth)acrylate compounds; and lactone-modified poly(meth)acrylate compounds having 4 or more functional groups in which a (poly)lactone structure has been introduced into the molecular structure of the aliphatic poly(meth)acrylate compounds.

[0071] Among these, the aromatic ring-containing (meth)acrylate compounds are preferred, and aromatic ring-containing mono(meth)acrylates are more preferred, because they provide excellent strength to molded articles and excellent impregnation properties into glass fibers.

[0072] In addition, the vinyl ester resin composition preferably contains a polyisocyanate compound, since it becomes a sheet molding compound with excellent handling properties such as peelability from a carrier film. The polyisocyanate compound may be used alone or in combination of two or more. The amount of the polyisocyanate compound added is preferably 5% by mass or more, more preferably 10% by mass or more, and is preferably 40% by mass or less, more preferably 30% by mass or less, based on the total mass of the vinyl ester resin and the polymerizable unsaturated group-containing compound.

[0073] The polyisocyanate compound may be any of the various compounds exemplified as those that may be contained in the epoxy resin composition. Among them, aromatic polyisocyanate compounds or various modified compounds thereof are preferred because they provide a sheet molding compound with excellent handling properties such as peelability from a carrier film. The isocyanate group content is preferably 15% by mass or more, more preferably 20% by mass or more, and is preferably 40% by mass or less.

[0074] The vinyl ester resin composition may contain a polymerization initiator. The polymerization initiator may be a general one without any particular limitation, but is preferably an organic peroxide. Examples of the organic peroxide include diacyl peroxide compounds, peroxyester compounds, hydroperoxide compounds, ketone peroxide compounds, alkyl perester compounds, percarbonate compounds, and peroxyketals. These polymerization initiators may be used alone or in combination of two or more. From the viewpoint of the balance between storage stability and curability, the amount of the polymerization initiator added is preferably 0.1% by mass or more, more preferably 0.2% by mass or more, and even more preferably 0.3% by mass or more, and more preferably 3% by mass or less, and more preferably 2% by mass or less, based on the total mass of the vinyl ester resin and the polymerizable unsaturated group-containing compound.

[0075] The vinyl ester resin composition may contain a polymerization inhibitor. Examples of the polymerization inhibitor include hydroquinone, trimethylhydroquinone, pt-butylcatechol, t-butylhydroquinone, toluhydroquinone, p-benzoquinone, naphthoquinone, hydroquinone monomethyl ether, phenothiazine, copper naphthenate, and copper chloride. These may be used alone or in combination of two or more. The amount of the polymerization inhibitor added is preferably in the range of 0.01 to 3 mass% based on the total mass of the vinyl ester resin and the polymerizable unsaturated group-containing compound.

[0076] In order to obtain excellent impregnation ability into glass fibers, the viscosity of the vinyl ester resin composition at 25°C is preferably 100 mPa·s or more, more preferably 300 mPa·s or more, and is preferably 10,000 mPa·s or less, more preferably 6,000 mPa·s or less. In this specification, the viscosity of the vinyl ester resin composition is measured within 10 minutes after all the ingredients of the vinyl ester resin composition are mixed.

[0077] In addition to the thermosetting resin, a thermoplastic resin may be used as the resin contained in the damping layer and the resin molding material (1). Examples of the thermoplastic resin include polyamide resin, polyacetal resin, aromatic polyester resin such as polyethylene terephthalate resin, polybutylene terephthalate resin, and polycarbonate resin, polyurethane resin, polyolefin resin such as polypropylene resin and polyethylene resin, polystyrene resin, acrylic resin, polyarylene sulfide resin, and those modified by copolymerization or the like. These may be used alone or in combination of two or more kinds.

[0078] The attenuation layer and the resin molding material (1) essentially contain graphite powder and glass fiber in addition to the thermosetting resin.

[0079] Compared with carbon nanotubes and carbon black used in conventional resin molding materials, graphite powder has fewer impurities and a higher carbon content, and therefore has superior electrical conductivity, so that the attenuation layer and the resin molding material (1) can have superior electromagnetic wave attenuation properties.

[0080] The graphite powder used has a volume average particle size of 20 nm or more and 200 μm or less. This volume average particle size is the particle size of the primary particles. The volume average particle size means the volume average particle size (D50) at which the volume accumulated value is 50% in the particle size distribution measured by a laser diffraction scattering method (for example, using HORIBA's LA-750). In the attenuation layer and the resin molding material (1), if the volume average particle size of the graphite powder is less than 20 nm, a small amount of the graphite powder cannot provide sufficient electromagnetic wave absorption ability, and if a large amount is added, the viscosity of the resin composition itself increases, making it difficult to impregnate the glass fiber. If the volume average particle size of the graphite powder exceeds 200 nm, it becomes difficult to uniformly disperse the graphite powder in the attenuation layer, and there are regions with a small amount of graphite powder and regions with a large amount of graphite powder, resulting in unevenness in the electromagnetic wave absorption ability. The particle size of the graphite powder is preferably 20 nm or more, 50 nm or more, 100 nm or more, 1 μm or more, or 2 μm or more, and is preferably 150 μm or less, 100 μm or less, 75 μm or less, 50 μm or less, or 25 μm or less. In order to obtain better electromagnetic wave attenuation, the volume average particle size of the graphite powder is more preferably 1 to 100 μm, and further preferably 2 to 75 μm.

[0081] The content of graphite powder is 2% by mass or more and 20% by mass or less based on the total mass of the electromagnetic wave attenuation layer or the resin molding material (1). This allows excellent electromagnetic wave attenuation to be obtained. If the graphite content is less than 2% by mass or more than 20% by mass, it becomes difficult to attenuate electromagnetic waves. The content of graphite is preferably 5% by mass or more and 10% by mass, and more preferably 18% by mass or less and 15% by mass or less.

[0082] The attenuation layer and the resin molding material (1) contain glass fibers, which ensure the thickness and strength of the attenuation layer itself, and suppress polymerization shrinkage during heat curing, thereby making it possible to obtain an attenuation layer of a desired thickness. The glass fiber content is 25% by mass or more and 55% by mass or less, based on the total mass of the electromagnetic wave attenuation layer or the resin molding material (1). This makes it possible to suppress the resin molding material (1) from flowing out of the mold when the resin molding material (1) is heated and pressurized in the mold, and a predetermined pressure can be applied to the resin molding material (1) in the mold, thereby suppressing the generation of bubbles and obtaining an attenuation layer with no unevenness in electromagnetic wave attenuation performance. If the glass fiber content is less than 25% by mass, it is not possible to suppress the resin molding material (1) from flowing out of the mold during heat molding, and bubbles are generated in the attenuation layer, resulting in uneven electromagnetic wave attenuation. On the other hand, if the glass fiber content exceeds 55% by mass, unimpregnated portions in which the resin composition is not sufficiently impregnated into the glass fibers are generated in the resin molding material (1). The air contained in the unimpregnated portion expands during the heat and pressure molding process, generating air bubbles in the resulting attenuation layer. The electromagnetic wave attenuation performance of the attenuation layer is inferior in the areas where air bubbles are present compared to areas where no air bubbles are present, resulting in unevenness in the electromagnetic wave attenuation performance of the attenuation layer.

[0083] Furthermore, by adjusting the glass fiber content, the position (frequency) of the peak wavelength of the electromagnetic wave attenuation can be adjusted to the lower or higher side. For example, when the glass fiber content is close to 25% by mass within the range of 25% by mass or more and 55% by mass or less, electromagnetic waves of lower frequencies in the 60 to 90 GHz frequency band can be attenuated, and when it is close to 55% by mass, electromagnetic waves of higher frequencies in the 60 to 90 GHz frequency band can be attenuated.

[0084] Examples of glass fibers include glass fiber aggregates such as chopped glass fiber mats, glass fiber woven fabrics, and glass fiber nonwoven fabrics. The thickness of the glass fiber aggregate may be appropriately set and selected depending on the thickness of the attenuation layer, which is a wavelength control factor of the electromagnetic waves to be attenuated. When ensuring the thickness of the attenuation layer using the glass fiber aggregate, the lamination process takes time and effort if there are many layers. Therefore, in order to reduce the number of layers, the thickness of the glass fiber aggregate is preferably, for example, 0.1 mm or more, 1 mm or more, or 2 mm or more. The basis weight of the glass fiber aggregate is 300 g / m 2 More than 350g / m 2 or more than 400g / m 2 It is preferable that the thickness is 600 g / m or more. 2 Below 550g / m 2 or less than 500g / m 2 It is preferable that:

[0085] When an SMC sheet is used as the resin molding material (1), the average length of the glass fibers contained in the resin molding material (1) is preferably 1 mm or more, 3 mm or more, or 5 mm or more in order to ensure the strength of the molded body, and is preferably 50 mm or less, 25 mm or less, or 15 mm or less in order to ensure fluidity in the mold during molding.

[0086] The average length of the glass fibers contained in the resin molding material (1) is measured by the following method. Approximately 20 mg of glass fiber is weighed out into a polyethylene cup and rubbed against the wall of the cup with a metal spatula to break it down. The glass fiber adhering to the wall of the cup is pressed onto one side of a weak adhesive double-sided tape to attach it to the tape. The other adhesive side of the double-sided tape to which the glass fiber has been attached is attached flat onto a white plastic sheet to create a sheet for microscopic observation. This sheet for microscopic observation is observed with the optical microscope equipment described below, and optical images are obtained. The distance obtained using the two-point distance measurement tool of the image analysis software described below is regarded as the length of the fiber. 100 glass fibers are randomly selected, their lengths are measured and recorded, and the number average length is calculated. As the optical microscope device, for example, a digital microscope VR-3200 manufactured by KEYENCE Corporation can be used, and the magnification of the microscope can be, for example, 12 to 40 times depending on the length of the glass fiber. As the analysis software, for example, software VR-3000 G2 observation application Ver2.4.0.115 (plane measurement-two-point distance measurement tool) manufactured by KEYENCE Corporation can be used.

[0087] In one embodiment of the present invention, the damping layer and the resin molding material (1) may further contain other components, such as fillers (excluding the above-mentioned graphite powder and glass fiber), low-shrinkage agents, release agents, thickeners, viscosity reducers, pigments, antioxidants, plasticizers, flame retardants, antibacterial agents, UV stabilizers, reinforcing materials, and photocuring agents.

[0088] In one embodiment of the present invention, the damping layer and the resin molding material (1) may further include an aggregate of fibers (hereinafter also referred to as a "fiber aggregate") other than the above-mentioned glass fibers, from the viewpoint of easily ensuring the thickness and strength of the damping layer. In this case, the fiber aggregate may be in a state of being impregnated with the above-mentioned resin (resin composition). Examples of the fiber aggregate include woven fabric, nonwoven fabric, cut fiber bundle mat, and paper body. The fiber aggregate may include at least one fiber selected from the group consisting of ceramic fibers, fibers derived from natural stones, and organic fibers. Examples of the ceramic fibers include alumina fibers, zirconia fibers, and boron fibers. Examples of the fibers derived from natural stones include basalt fibers. Examples of the organic fibers include polyester fibers, polypropylene fibers, polyamide fibers, polyarylene sulfide fibers, and natural organic fibers.

[0089] In one embodiment of the present invention, the thickness of the attenuation layer is preferably 0.5 mm or more and 5 mm or less. This makes it possible to control the peak wavelength of electromagnetic wave attenuation in the frequency range of 60 to 90 GHz. The smaller the thickness of the attenuation layer, the higher the frequency band of electromagnetic waves that can be attenuated.

[0090] The resin molded body may include only the electromagnetic wave attenuation layer, or may further include a layer other than the electromagnetic wave attenuation layer. In one embodiment, the resin molded body may include an electromagnetic wave reflecting layer in addition to the electromagnetic wave attenuation layer.

[0091] Fig. 1 is a schematic cross-sectional view showing one embodiment of a resin molded body. As shown in Fig. 1, a resin molded body 1 according to one embodiment includes an electromagnetic wave attenuation layer 2 and an electromagnetic wave reflecting layer 3 laminated on the electromagnetic wave attenuation layer 2. In this embodiment, the electromagnetic wave reflecting layer 3 is disposed directly on the electromagnetic wave attenuation layer 2, that is, without any other layer being interposed therebetween. In another embodiment, another layer (e.g., a spacer) may be provided between the electromagnetic wave attenuation layer and the electromagnetic wave reflecting layer.

[0092] The electromagnetic wave reflection layer (hereinafter, simply referred to as "reflection layer") is a layer capable of reflecting electromagnetic waves. The reflection layer may be formed of a material having a characteristic impedance different from that of the attenuation layer (the characteristic impedance is expressed by the dielectric constant and the magnetic permeability), for example, it may be formed of a resin, and more preferably, it is formed of a material rich in free electrons, which can greatly change the characteristic impedance of the reflection layer, since higher reflection characteristics can be obtained. In this case, the resin molding is particularly suitable for use in applications in which external electromagnetic waves are shielded by the electromagnetic wave reflection layer.

[0093] In one embodiment, the reflective layer may contain a metal, or may contain a compound or fiber with a graphite structure. Examples of metals include aluminum, iron, nickel, copper, silver, and alloys thereof. The reflective layer containing a metal may be, for example, a plate, foil, film containing fine particles, plated film, net, perforated plate, or a box such as a casting made of the metal or alloy.

[0094] In another embodiment, the reflective layer may include resin and carbon fiber. That is, the resin molded body may include a reflective layer containing resin and carbon fiber. In this case, the resin molded body is obtained by molding a resin molding material (hereinafter also referred to as "resin molding material (2)") containing resin and carbon fiber for forming the reflective layer. The resin contained in the resin molding material (2) may be the same as or different from the thermosetting resin (including a resin composition) described as the resin contained in the attenuation layer and the resin molding material (1).

[0095] The carbon fibers used in the reflective layer and the resin molding material (2) may be monofilaments or may be in the form of a carbon fiber bundle. When the carbon fibers are in the form of a carbon fiber bundle, the carbon fiber bundle may be, for example, monofilaments bound together with a bundling agent (sizing agent). The number of filaments in the carbon fiber bundle may be, for example, 1,000 or more and 60,000 or less.

[0096] From the viewpoint of achieving both electromagnetic wave reflection performance and fluidity in a mold during molding, when an SMC sheet is used as the resin molding material (2), the average length of the carbon fibers contained in the resin molding material (2) is preferably 1 mm or more, 3 mm or more, or 5 mm or more, and is preferably 50 mm or less, 25 mm or less, or 15 mm or less.

[0097] The average length of the carbon fibers contained in the reflective layer and the resin molding material (2) is measured by the following method. Approximately 20 mg of carbon fiber is weighed into a polyethylene cup and rubbed against the cup wall with a metal spatula to defibrate it. The carbon fiber attached to the cup wall is pressed onto one side of a weak adhesive double-sided tape to attach it to the tape. The other side of the double-sided tape to which the carbon fiber has been attached is attached flatly to a white plastic sheet to create a sheet for microscopic observation. This sheet for microscopic observation is observed with the following optical microscope device to obtain an optical image. Since carbon fibers of 1 to 5 mm can be observed in an almost straight state, the distance obtained using the two-point distance measurement tool of the following image analysis software is regarded as the length of the fiber. 100 carbon fibers are randomly selected, their lengths are measured and recorded, and the number average length is calculated. As the optical microscope device, for example, a digital microscope VR-3200 manufactured by KEYENCE Corporation can be used, and the magnification of the microscope can be, for example, 12 to 40 times depending on the length of the carbon fiber. As the analysis software, for example, software VR-3000 G2 observation application Ver2.4.0.115 (plane measurement-two-point distance measurement tool) manufactured by KEYENCE Corporation can be used.

[0098] Furthermore, when it is necessary to separate and recover the carbon fibers from the reflective layer or the resin molding material (2) when measuring the average length of the carbon fibers, the carbon fibers are separated and recovered by the following method. The reflective layer or resin molding material (2) containing carbon fibers is placed in a magnetic crucible and heated in air in a muffle furnace set at 150°C for 1 hour, then heated to 550°C and heated for an additional 2.5 hours. After cooling, the carbon fibers can be separated and recovered from the residue in the crucible.

[0099] From the viewpoint of achieving both electromagnetic wave reflection performance and fluidity in a mold during molding, the content of carbon fibers in the reflective layer and the resin molding material (2) is preferably 1 mass % or more, 5 mass % or more, or 10 mass % or more, based on the total mass of the reflective layer or the resin molding material (2), and is preferably 55 mass % or less, 50 mass % or less, or 45 mass % or less.

[0100] The thickness of the reflective layer can be appropriately set depending on the desired shape and strength, and may be, for example, 0.5 mm or more, 1 mm or more, or 2 mm or more, and may be 5 mm or less, 3 mm or less, or 2.5 mm or less.

[0101] The shape of the resin molding having the attenuation layer and the reflection layer is arbitrary, and may be a sheet-like shape or a three-dimensional shape such as a box. In one embodiment, the attenuation layer can be produced by curing a sheet-like resin molding material (1). In one embodiment, the reflection layer can be produced by curing a sheet-like resin molding material (2). From the viewpoint of excellent moldability and ease of molding into a box such as a housing of a millimeter wave radar, it is preferable that the attenuation layer and the reflection layer are produced from the sheet-like resin molding material (1) and the sheet-like resin molding material (2), respectively. From the viewpoint of ease of work, ease of handling, etc., the sheet-like resin molding material (1) and the sheet-like resin molding material (2) are preferably sheet molding compounds or prepregs.

[0102] The resin molded body having the damping layer of this embodiment can be obtained, for example, by a manufacturing method including (A) a resin molding material manufacturing step and (B) a resin molded body manufacturing step.

[0103] (A) Manufacturing process of resin molding material In this step (A), for example, a thermosetting resin composition is mixed with commercially available graphite powder, and the resulting mixture is stirred to form a conductive filler-containing resin composition, which is then impregnated into a glass fiber assembly by pressure or other means to obtain a resin molding material (1). The resin molding material (1) thus obtained is called an SMC (sheet molding compound) sheet or prepreg.

[0104] (B) Manufacturing process of resin molded products In this step (B), the resin molding material (1) obtained in step (A) is cured to form a resin molded body. More specifically, the resin molding material (1) that is smaller than the projected area of ​​the cavity of the mold and thicker than the cavity thickness is placed in the cavity. Next, the mold is clamped to pressurize the resin molding material (1), thereby filling the cavity with the resin molding material (1) to form it. There are no particular limitations on the molding means. For example, by applying heat and pressure using a heated press machine, the thermosetting resin contained in the resin molding material (1) is crosslinked to obtain a resin molded body.

[0105] In the following, as a more specific example of a method for manufacturing a resin molded body, a manufacturing method will be described in which an attenuation layer and a reflective layer are molded by laminating sheet-shaped resin molding materials (1) and (2).

[0106] First, a thermosetting resin, graphite powder, a curing agent, etc. are stirred and mixed to prepare a resin composition used in the resin molding material (1). Next, the resin composition is applied onto a carrier film, and a glass fiber layer is placed thereon. Another set of carrier films coated with the resin composition is prepared, and the resin composition is laminated in the order of carrier film / resin composition / glass fiber layer / resin composition / carrier film, and the resin composition is impregnated into the glass fiber layer using a pressure roll or the like to prepare the resin molding material (1). After pressing with a pressure roll or the like, the resin composition may be allowed to stand for 10 hours or more in a temperature range of room temperature (e.g., 25°C) to about 50°C to be aged.

[0107] On the other hand, a resin composition used for the resin molding material (2) is prepared by stirring and mixing a thermosetting resin, a curing agent, etc. Next, the resin composition is applied onto a carrier film, and a carbon fiber layer is placed thereon. Another set of the resin composition applied onto the carrier film is prepared, and these are laminated in the order of carrier film / resin composition / carbon fiber layer / resin composition / carrier film, and the resin composition is impregnated into the carbon fiber layer with a pressure roll or the like to prepare the resin molding material (2). After pressing with a pressure roll or the like, the mixture may be allowed to stand for 10 hours or more in a temperature range of room temperature (for example, 25°C) to about 50°C to be aged.

[0108] For example, the obtained resin molding material (1) and the resin molding material (2) are stacked and placed in a mold, and then heated and pressurized to harden the laminate. At this time, the thickness of the resulting attenuation layer can be adjusted by adjusting the number of layers of the resin molding material (1) and the height of the mold cavity. Similarly, the thickness of the resulting reflection layer can be adjusted by adjusting the number of layers of the resin molding material (2) and the thickness of the mold cavity. The resin molded body thus manufactured is a molded body consisting of two layers, the electromagnetic wave attenuation layer and the electromagnetic wave reflection layer. The electromagnetic wave attenuation layer is a resin molded body formed by molding the resin molding material (1), and the electromagnetic wave reflection layer is a resin molded body formed by molding the resin molding material (2).

[0109] The resin molding material (1) and the resin molding material (2) may be stacked and cured in a mold, or one of the resin molding materials may be first heat-cured in the mold and then the other resin molding material may be stacked on the cured product and cured by heat. For example, the resin molding material (1) may be first cured in the mold, and after the mold is opened once, the resin molding material (2) may be placed on top of the cured resin molding material (1) and the mold may be closed again to cure the resin molding material (2).

[0110] The resin molded body of the present embodiment is used in various applications that require attenuation (absorption) of electromagnetic waves. In this case, the resin molded body is molded into a sheet (electromagnetic wave attenuation sheet, electromagnetic wave absorbing sheet) or a housing (housing for electronic devices) and can be used as an electromagnetic wave attenuator (electromagnetic wave absorber). The resin molded body can be used as an electromagnetic wave attenuator (electromagnetic wave absorber) for, for example, electronic devices such as smartphones, tablet terminals, and personal computers, millimeter wave radar devices, building materials such as building materials walls and window glass, vehicles, ships, and aircraft, etc., in which electromagnetic waves need to be absorbed. In addition, the resin molded body can also be used as an electromagnetic wave attenuator (electromagnetic wave absorber) by joining it to a flexible printed wiring board, a rigid printed wiring board, a COF, a TAB, a flexible connector, a liquid crystal display, a touch panel, etc. In addition, the resin molded body can also be used as an electromagnetic wave attenuator (electromagnetic wave absorber) for use in an electronic toll collection system (ETC) on a highway and installed on the roof of a toll booth or between ETC lanes. EXAMPLES

[0111] The present invention will be described in more detail below based on examples, but the present invention is not limited to these examples. EXAMPLES

[0112] <Preparation of Resin Composition for Damping Layer> The damping resin composition was prepared as follows. First, a vinyl ester resin paste was prepared by stirring and mixing a bisphenol A type vinyl ester resin (Exdoma (registered trademark) manufactured by DIC Materials Co., Ltd.) and phenoxyethyl methacrylate (flash point 120°C) as the polymerizable unsaturated group-containing compound. Next, polyisocyanate (Lupranate (registered trademark) MI manufactured by BASF INOAC Polyurethanes Co., Ltd.) was added and mixed well at room temperature, and then graphite powder a (artificial graphite SGP-3 manufactured by SEC Carbon Co., Ltd., volume average particle size 3 μm) was further added and mixed. Furthermore, a polymerization initiator (Kayacarbon AIC-75, organic peroxide manufactured by Kayaku Akzo Co., Ltd.) and parabenzoquinone as a polymerization inhibitor were added and stirred well at room temperature to obtain a damping layer resin composition. The compounding ratio (mass ratio) of each component contained in the damping resin composition is shown in Table 1.

[0113] <Preparation of resin molding material (1)> The obtained resin composition for the damping layer, 70 g, was divided into approximately half and each half was applied to a square area of ​​30 cm square of a polypropylene casting film. Then, 46 g of glass fiber (PB-549 manufactured by Nittobo Co., Ltd., weight per unit area 4.8 g / m) cut into 2 cm lengths was uniformly spread on the surface coated with the resin composition for the damping layer to form a glass fiber layer. The remaining half of the divided resin composition for the damping layer was similarly applied to a 30 cm square area of ​​a polypropylene casting film, and the applied surface was overlapped so as to contact the glass fiber layer to obtain a laminate. Next, the laminate was pressed with a hand roller to sufficiently impregnate the resin composition for the damping layer into the glass fiber layer, and aged at room temperature for 24 hours or more to obtain a resin molding material (1) which is a sheet molding compound provided with a casting film on both sides. The resin molding material (1) obtained in this example had a glass fiber content of 40 mass% based on the total mass of the resin molding material (1).

[0114] <Preparation of resin molding material (2)> Sheet-shaped carbon fiber / resin molding material (DICARBO (registered trademark) CF manufactured by DIC Corporation, basis weight 2 kg / m 2A vinyl ester resin composition, a carbon fiber content of 45 mass%, and a polymerization initiator content of 0.8 mass% were cut into a 30 cm square using a rolling cutter to obtain a resin molding material (2), which is a sheet molding compound with process films on both sides.

[0115] <Preparation of resin molded body> The obtained resin molding material (1) and resin molding material (2) were heated and pressurized in a mold as follows to produce a resin molded body. The mold was composed of a convex upper mold and a concave lower mold, and had a cavity of 30 cm in length and 30 cm in width, and the height of the cavity was adjustable by a spacer. By adjusting the height of the cavity, the thickness of the obtained molded body, i.e., the thickness of each of the attenuation layer and the reflection layer, could be adjusted.

[0116] In this embodiment, the cavity height was set to 0.8 mm, and a 30 cm square resin molding material (1) was placed in the center of the cavity of the mold. The mold was closed, and the temperature of the upper mold was set to 140° C., the temperature of the lower mold was set to 150° C., and pressure was applied for 10 minutes under the condition of 92t to obtain an electromagnetic wave attenuation layer having a thickness of 0.8 mm. The mold was then opened, and the cavity height was set to 2.8 m, and two sheets of the 30 cm square resin molding material (2) were placed on the hardened electromagnetic wave attenuation layer. The mold was closed again, and the temperature of the upper mold was set to 140° C., the temperature of the lower mold was set to 150° C., and pressure was applied for 10 minutes under the condition of 92t to obtain a resin molded body in which an electromagnetic wave reflection layer was formed on the electromagnetic wave attenuation layer. The obtained resin molded body had an attenuation layer thickness of 0.8 mm and a reflection layer thickness of 2.0 mm. When the resin molded body was visually observed, no polymerization shrinkage was observed in either the attenuation layer or the reflection layer. The same applies to other embodiments and comparative examples. Furthermore, the obtained resin molding has excellent heat resistance since it is mainly composed of vinyl ester resin.

[0117] <Measurement of electromagnetic wave attenuation> A 15 cm square area was cut out from the center of the obtained resin molded body to obtain a test piece for measuring electromagnetic wave attenuation. The test piece was used to measure electromagnetic wave attenuation (electromagnetic wave reflection attenuation and electromagnetic wave transmission attenuation). The S parameters were measured by the free space method using the following device configuration. RF measuring instrument: Keysight Technologies vector network analyzer N5290A Measurement fixture: S-parameter method measurement fixture FS110 type (EM Lab's horn antenna with dielectric lens (for E band) and sample stand)

[0118] The electromagnetic wave was incident on the test piece perpendicularly to the attenuation layer side of the test piece. The frequency of the electromagnetic wave was modulated in the range of 60 to 90 GHz. A reference metal plate (2 mm aluminum plate) was placed on the sample stand, and the angle of the horn antenna was adjusted so that the reception level at the reference metal plate was maximized. In addition, the electromagnetic wave attenuation on the reflection side (electromagnetic wave reflection attenuation) and the electromagnetic wave attenuation on the transmission side (electromagnetic wave transmission attenuation) were calculated from the difference (L1-L2) between the reception level L1 when the test piece for measuring electromagnetic wave attenuation was placed on the sample stand and the reception level L2 when the reference metal plate was placed on the sample stand. The measured electromagnetic wave reflection attenuation is shown in Table 1. The electromagnetic wave transmission attenuation was -40 dB or more not only for the test piece of this example but also for the test pieces of other examples and comparative examples.

[0119] <Evaluation of blister generation amount> The surface of the damping layer was visually observed, and the amount of blisters on the surface of the damping layer was evaluated based on the following criteria. The results are shown in Table 1. <<Evaluation>> A: Attenuation layer surface 1m 2 Less than 5 bubbles per unit B: Attenuation layer surface 1m 2 Generates 6-9 bubbles per C: Attenuation layer surface 1m 2 More than 10 bubbles per unit

[0120] <Measurement of bending strength> Test pieces for measuring bending strength were cut out from the obtained resin molded product and subjected to a three-point bending test in accordance with JIS K 7074. The results are shown in Table 1. EXAMPLES

[0121] In this example, 70 g of the resin composition for the damping layer was prepared according to the compounding ratio shown in Table 1 of the following example, and 46 g of glass fiber was scattered on it, but the resin molding material (1) was prepared exactly the same as in Example 1. Then, a resin molding and a test piece were prepared exactly the same as in Example 1, and the above-mentioned measurements and evaluations were carried out. The results are shown in Table 1. EXAMPLES

[0122] In this example, a resin molding material (1) was produced in exactly the same manner as in Example 1, except that graphite powder b (Tokai Carbon Co., Ltd., Toka Black #3845, volume average particle size 40 nm) was used instead of graphite powder a, and 70 g of the resin composition for the damping layer was prepared in the blending ratio shown in Table 1 of the following example, and 46 g of glass fiber was scattered on it. Then, a resin molding and a test piece were produced in exactly the same manner as in Example 1, and the above-mentioned measurements and evaluations were carried out. The results are shown in Table 1. EXAMPLES

[0123] In this example, 80 g of the resin composition for the damping layer was prepared according to the compounding ratio shown in Table 1 of the following example, and 35 g of glass fiber was scattered on it, but the resin molding material (1) was prepared exactly the same as in Example 1. Then, a resin molding and a test piece were prepared exactly the same as in Example 1, and the above-mentioned measurements and evaluations were carried out. The results are shown in Table 1. EXAMPLES

[0124] In this example, 57 g of the resin composition for the damping layer was prepared according to the compounding ratio shown in Table 1 of the following example, and 57 g of glass fiber was scattered on the resin molding material (1) in exactly the same manner as in Example 1. Then, a resin molding and a test piece were prepared in exactly the same manner as in Example 1, and the above-mentioned measurements and evaluations were carried out. The results are shown in Table 1. EXAMPLES

[0125] In this example, 103 g of the resin composition for the attenuation layer was prepared according to the compounding ratio shown in Table 2 of the following example, and 68 g of glass fiber was scattered, except that a resin molding material (1) was produced in exactly the same manner as in Example 1. Next, a resin molding and a test piece were produced in exactly the same manner as in Example 1, except that the cavity height when molding the electromagnetic wave attenuation layer was adjusted to 1.2 mm, and the cavity height when molding the electromagnetic wave reflection layer was adjusted to 3.2 mm, and the above-mentioned measurements and evaluations were performed. The obtained resin molding had an attenuation layer thickness of 1.2 mm and a reflection layer thickness of 2.0 mm. The results are shown in Table 2. EXAMPLES

[0126] In this example, 103 g of the resin composition for the attenuation layer was prepared according to the compounding ratio shown in Table 2 of the following example, and 68 g of glass fiber was scattered, except that a resin molding material (1) was produced in exactly the same manner as in Example 1. Next, a resin molding and a test piece were produced in exactly the same manner as in Example 1, except that the cavity height when molding the electromagnetic wave attenuation layer was adjusted to 1.2 mm, and the cavity height when molding the electromagnetic wave reflection layer was adjusted to 3.2 mm, and the above-mentioned measurements and evaluations were carried out. The results are shown in Table 2. EXAMPLES

[0127] In this example, 171 g of the resin composition for the attenuation layer was prepared according to the compounding ratio shown in Table 2 of the following example, and 114 g of glass fiber was scattered, except that a resin molding material (1) was produced in exactly the same manner as in Example 1. Next, a resin molding and a test piece were produced in exactly the same manner as in Example 1, except that the cavity height when molding the electromagnetic wave attenuation layer was adjusted to 2.0 mm, and the cavity height when molding the electromagnetic wave reflection layer was adjusted to 4.0 mm, and the above-mentioned measurements and evaluations were performed. The obtained resin molding had an attenuation layer thickness of 2.0 mm and a reflection layer thickness of 2.0 mm. The results are shown in Table 2. EXAMPLES

[0128] In this example, graphite powder c (manufactured by SEC Carbon Co., Ltd., artificial graphite SGP-50, volume average particle size 50 um) was used instead of graphite powder a, and 86 g of the resin composition for the attenuation layer was prepared in the blending ratio shown in Table 2 of the following example, and 57 g of glass fiber was scattered. The resin molding material (1) was produced in exactly the same manner as in Example 1, except that the height of the cavity when molding the electromagnetic wave attenuation layer was adjusted to 1.0 mm, and the height of the cavity when molding the electromagnetic wave reflection layer was adjusted to 3.0 mm. The resin molding and test pieces were then produced in exactly the same manner as in Example 1, and the above-mentioned measurements and evaluations were performed. The obtained resin molding had a thickness of 1.0 mm for the attenuation layer and a thickness of 2.0 mm for the reflection layer. The results are shown in Table 2.

[0129] [Comparative Example 1] In this comparative example, 69 g of the resin composition for the damping layer was prepared according to the compounding ratio shown in Table 3 of the following example, and 45 g of glass fiber was scattered on it, but the resin molding material (1) was produced in exactly the same manner as in Example 1. Then, a resin molding and a test piece were produced in exactly the same manner as in Example 1, and the above-mentioned measurements and evaluations were carried out. The results are shown in Table 3.

[0130] [Comparative Example 2] In this comparative example, the resin molding material (1) was produced in exactly the same manner as in Example 1, except that graphite powder b was used instead of graphite powder a, 69 g of the resin composition for the damping layer was prepared in the compounding ratio shown in Table 3 of the following example, and 45 g of glass fiber was scattered on it. Then, in exactly the same manner as in Example 1, a resin molding and a test piece were produced, and the above-mentioned measurements and evaluations were carried out. The results are shown in Table 3.

[0131] [Comparative Example 3] In this comparative example, graphite powder d (manufactured by Nippon Graphite Industries Co., Ltd., artificial graphite, PAG-60, volume average particle size 350 um) was used instead of graphite powder a, and 69 g of the resin composition for the damping layer was prepared in the compounding ratio shown in Table 3 of the following example, and 45 g of glass fiber was sprinkled on it. The resin molding material (1) was produced in exactly the same manner as in Example 1. Then, a resin molding and a test piece were produced in exactly the same manner as in Example 1, and the above-mentioned measurements and evaluations were carried out. The results are shown in Table 3.

[0132] [Comparative Example 4] In this comparative example, 91 g of the resin composition for the damping layer was prepared according to the compounding ratio shown in Table 3 of the following example, and 23 g of glass fiber was scattered on it, but the resin molding material (1) was produced exactly the same as in Example 1. Then, a resin molding and a test piece were produced exactly the same as in Example 1, and the above-mentioned measurements and evaluations were carried out. The results are shown in Table 3.

[0133] [Comparative Example 5] In this comparative example, 46 g of the resin composition for the damping layer was prepared according to the compounding ratio shown in Table 3 of the following example, and 68 g of glass fiber was scattered, except for which a resin molding material (1) was produced in exactly the same manner as in Example 1. Then, a resin molding and a test piece were produced in exactly the same manner as in Example 1, and the above-mentioned measurements and evaluations were carried out. The results are shown in Table 3.

[0134] [Table 1]

[0135] [Table 2]

[0136] [Table 3]

[0137] The resin molded bodies of Examples 1 to 9 all have an electromagnetic wave attenuation layer containing a thermosetting resin, graphite powder, and glass fibers, the volume average particle size of the graphite powder being in the range of 40 nm to 50 μm, the graphite powder content being in the range of 4.3 mass % to 18.3 mass % based on the total mass of the electromagnetic wave attenuation layer, and the glass fiber content being in the range of 30 mass % to 50 mass % based on the total mass of the electromagnetic wave attenuation layer. As shown in Tables 1 and 2, the resin molded bodies of Examples 1 to 9 all have excellent electromagnetic wave attenuation properties. Furthermore, the resin molding material used to form the electromagnetic wave attenuation layer provided on the resin molded bodies of Examples 1 to 9 can suppress polymerization shrinkage.

[0138] On the other hand, the resin molding of Comparative Example 1 has an excessively high graphite powder content of 50 mass%, the resin molding of Comparative Example 2 has an excessively low graphite powder content of 3 mass% based on the total mass of the electromagnetic wave attenuation layer, and the resin molding of Comparative Example 3 has an excessively high volume average particle size of graphite powder of 350 μm. The resin moldings of Comparative Examples 1 to 3 are inferior in electromagnetic wave attenuation property. The resin molding of Comparative Example 4 has an insufficient glass fiber content of 20 mass % based on the total mass of the electromagnetic wave attenuation layer, while the resin molding of Comparative Example 5 has an excessive glass fiber content of 60 mass % based on the total mass of the electromagnetic wave attenuation layer. As shown in Table 3, many air bubbles were observed in the attenuation layer of the resin moldings of Comparative Examples 4 to 5. This shows that the resin moldings of Comparative Examples 4 to 5 have uneven electromagnetic wave attenuation property and are inferior in electromagnetic wave attenuation property.

[0139] Furthermore, the resin moldings of Examples 1 and 6 use the same resin molding material (1) for the attenuation layer, but have different thicknesses of the attenuation layer. It can be seen from Tables 1 and 2 that the resin molding of Example 1, which has an attenuation layer thickness of 0.8 mm, can attenuate electromagnetic waves in a higher frequency band than the resin molding of Example 6, which has an attenuation layer thickness of 1.2 mm. [Explanation of symbols]

[0140] 1...resin molding, 2...electromagnetic wave attenuation layer, 3...electromagnetic wave reflecting layer.

Claims

1. An electromagnetic wave attenuation layer including a thermosetting resin, graphite powder, and glass fiber; The graphite powder has a volume average particle size of 20 nm or more and 200 μm or less, The content of the graphite powder is 2% by mass or more and 20% by mass or less based on the total mass of the electromagnetic wave attenuation layer, A resin molded article, the content of glass fibers being 25% by mass or more and 55% by mass or less based on the total mass of the electromagnetic wave attenuation layer.

2. 2. The resin molded article according to claim 1, wherein the graphite has a volume average particle size of 1 μm or more and 100 μm or less.

3. 3. The resin molding according to claim 1, wherein the electromagnetic wave attenuation layer has a thickness of 0.5 mm or more and 3 mm or less.

4. 3. The resin molded article according to claim 1, wherein the thermosetting resin comprises at least one selected from the group consisting of an epoxy resin and a vinyl ester resin.

5. The resin molded article according to claim 1 , further comprising an electromagnetic wave reflective layer.

6. The resin molded article according to claim 5 , wherein the electromagnetic wave reflective layer contains a thermosetting resin and carbon fibers.

7. The resin molding according to claim 5, which is used as an electromagnetic wave attenuation sheet or a housing for electronic equipment.

8. A resin molding material comprising a thermosetting resin, graphite powder, and glass fibers, The graphite powder has a volume average particle size of 200 μm or less, The content of the graphite powder is 2% by mass or more and 20% by mass or less based on the total mass of the resin molding material, A resin molding material having a glass fiber content of 25% by mass or more and 55% by mass or less based on the total mass of the resin molding material.

Citation Information

Patent Citations

  • Electromagnetic shielding material and signal processing unit provided with same

    WO2019235561A1